Safe flight to which haven when Russia invades Ukraine? a 48-hour story - Mohamad, Azhar (Elsevier, 2022)
We examine the flight-to-safety phenomenon from ruble (risky asset) to other safe-haven assets at the onset of the Russian invasion of Ukraine on 24 February 2022. We find evidence of flight-to-safe-haven occurrences from the ruble to the USD, yen, silver, Brent, WTI and natural gas as indicated by negative dynamic conditional correlations between these assets. Price discovery surrounding the invasion is found to be dominated by Brent and bitcoin. Further, we observe the presence of herding behaviours between energy commodities (Brent, WTI, gasoline and natural gas) and cryptocurrencies (bitcoin, ethereum and litecoin).